FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP KECURANGAN AKUNTANSI DENGAN PERILAKU TIDAK ETIS SEBAGAI VARIABEL INTERVENING PADA STAF ACCOUNTING PERUSAHAAN DAGANG DI SEMARANG - Fitri Apriliasari; Sri Wiranti setiyanti; Zumrotun Nafiah (Sekolah Tinggi Ilmu Ekonomi Semarang, 2020)
One of the negative impacts of the development of accounting science is accounting fraud. This has been experienced by PT Garuda Indonesia Tbk, which made a misstatement in the presentation of financial statements, resulting in suspicions of accounting fraud in the presentation of the financial statements. The purpose of this study is to determine the effect of internal control effectiveness, compensation suitability, and individual morality on accounting fraud with unethical behavior as an intervening variable in accounting staff of a trading company in Semarang. The population of this research is accounting staff of trading companies in Semarang. The sample of this research was 50 accounting staff who were selected by using purposive sampling method. The variables of this study consist of independent variables (effectiveness of internal control, suitability of compensation and individual morality), dependent variables (accounting fraud) and intervening variables (unethical behavior). This research data collection method is a questionnaire. The data analysis in this study used Structural Equation Modeling based on Partial Least Square (SEM-PLS) with the SmartPLS 3.0 analysis tool and the coefficient of determination R-Square (R2) and t test using the Boostrapping method. The results showed that the effectiveness of internal control and individual morality did not have a significant effect on unethical behavior, this can be proven by the negative original sample values, namely -0.193 and -0.001 respectively and the t-statistic value respectively 0.875 and 0.007 which < 1.96. Compensation suitability has a negative and significant effect on unethical behavior, with a negative original sample value of -0.389 and a t-statistic value of 2.490> 1.96. The effectiveness of internal control and individual morality has a negative and significant effect on accounting fraud, with negative original sample values ​​of -0.416 and -0.366 respectively and t-statistic values ​​of 4.253 and 3.550> 1.96, respectively. Compensation suitability has no significant effect on accounting fraud, with a negative original sample value of -0.002 and a t-statistic value of 0.015 which is <1.96. Meanwhile, unethical behavior has a positive and significant effect on accounting fraud, with a positive original sample value of 0.303 and a t-statistic value of 2.622> 1.96. Suggestions from this study are for further research to multiply other variables that affect accounting fraud and for trading companies in Semarang to better understand accounting fraud, the effectiveness of internal controls, suitability of compensation, individual morality, and unethical behavior so that in the future it can become a company that is clean with the principle of transparency.